Legal Analysis of The Financing Agreement Through The Application For Legal Examination The Fiduciary Guarantee Act The Constitutional Court - Sipayung, Iskandar Muda (SASI, 2023)
Introduction: The occurrence of legal problems related to objects that become fiduciary security, where some existing and well-known consumer finance institutions (leasing) often deal with the law, which is caused by default/inkar promises by consumers as fiduciary rights providers, so that leasing often deals with the authorities diakarenakan in taking action against delinquent consumers.Purposes of the Research: The purpose of this study is to explain the paradigm of material testing on the legal protection of fiduciary.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: Legal arrangements are needed for legal protection for consumer finance institutions (leasing) in obtaining fiduciary guarantees which in accordance with the agreement between leasing and consumers, are entitled to and belong to the institution if the consumer has defaulted/inkar promise, so that it can return the creditor, can be auctioned to the public, so that it does not have an impact on the economy, both from the company's revenue and the sustainability of the financing industry in Indonesia.